The Role of Vitamin D Metabolite Deficiency in the Development of Structural and Functional Disorders in Coxarthrosis - Kalashnikov, O.V.; Gayko, G.V.; Burianov, O.A.; Tymochuk, V.V.; Poluliakh, D.M. (TERRA ORTHOPAEDICA, 2021)
Summary. At present, there is a need to systematize the data of our own comprehensive research and literature in order to determine the role of active metabolites of vitamin D in the formation of structural and functional disorders (SFD) in osteoarthritis of the hip. Objective: on the basis of our own complex researches and data of literature, to determine the role of the insufficiency of vitamin D metabolites in the development of SFD in coxarthrosis. Materials and Methods. The basis for determining the role of active metabolites of vitamin D in the development of SFN in coxarthrosis was our own comprehensive studies of 506 patients with osteoarthritis of the hip and data from the literature. Results. On the basis of the theory of functional systems, a conceptual model for the development of SFD in coxarthrosis has been developed. The leading factor in the development of SFD in the rapid progression of idiopathic and dysplastic osteoarthritis of the hip is the lack of active metabolites of vitamin D. The presence of undifferentiated connective tissue dysplasia in turn causes a decrease in the absorption of provitamin D in the stomach and intestines. With a slow progression of idiopathic coxarthrosis, the leading factor in the development of these disorders is the excessive load on the hip joint. Factors of violation of biomechanical conditions and injury of the hip joint are factors of the progression of coxarthrosis of dysplastic and post-traumatic genesis. Pathogenic factors lead to functional and structural changes in systems of different levels and their elements with the development of inverted processes in the structures of the hip joint. Conclusions. Insufficiency of vitamin D metabolites on the background of undifferentiated connective tissue dysplasia leads to biochemical changes in articular cartilage and serum, affects both osteo- and chondrogenesis, leads to reduced immune status of patients and the development of clinical manifestations of rapid progression of idiopathic and dysplastic coxarthrosis. With a slow progression of idiopathic coxarthrosis, the main factor leading to the development of the above mentioned disorders is the excessive load on the hip joint. Factors of violation of biomechanical conditions and injury of the hip joint determine the development of SFD in coxarthrosis of dysplastic and post-traumatic genesis.